Neonatal hepatitis in a term newborn: sequelae to in utero COVID-19 infection - Kaur, Pushwinder (International Journal of Contemporary Pediatrics, 2021)
Neonatal hepatitis is a common disease entity seen among newborns. It is known as inflammation of liver parenchyma in newborns, specifically in first month of life. Most common cause of neonatal hepatitis is viral infection which infects liver in utero or in postnatal period. Newborns carrying neonatal hepatitis mostly present with jaundice, failure to gain weight and hepatosplenomegaly. Neonatal hepatitis due to in utero COVID infection is diagnosed by conjugated hyperbilirubinemia, raised SGOT and SGPT levels and raised COVID antibody levels. Treatment includes addition of fat-soluble vitamins, phenobarbitone and supportive care. Here author is reporting a rare case of 11 days old newborn with neonatal hepatitis, who presented with severe jaundice (TSB/DB- 44/22) hepatosplenomegaly and hypoxemia with mild respiratory distress. Maternal history revealed high grade fever with low cell count during 5th month of gestation, though COVID RAT was negative and RT-PCR was not done. Baby was managed in NICU with IV antibiotics, IV fluids, oxygen by prongs, oral fat-soluble vitamin supplementation, adequate calorie intake and phenobarbitone. Baby responded very well to the treatment and discharged in healthy condition after 7 days. Paucity of data documenting in utero COVID-19 infection as cause of neonatal hepatitis led us to report this rare case.